Agricultural Commodity Zakat: Aspects of the Determination of 'Illat Law and Maṣlahah' - Yenni Batubara (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
Nowadays, agricultural commodities are experiencing rapid growth and development with new agricultural innovations such as grafted plants and cross-breeding plants to more modern agriculture, namely hydroponics. This condition causes the agricultural products able to increase the income of farmers significantly. Agricultural products in Islamic law are one type of property that is obligatory for zakat. However, the arguments governing agricultural zakat only mention some agricultural products that are obligatory on zakat, including Jawawud, Wheat, Dates, and Raisins, so some agricultural commodities are out of the reach in these arguments, so there are no legal provisions. This research aims to see how to determine the legal provisions of zakat on agricultural or plantation commodities. This research is using literature studies method. The results of this study indicate that the product of agricultural commodities that have high economic value are qiyās on the types of fruits and grains that are obligatory for zakat, mentioned in the arguments of the Al-Qur' ān and Sunnah with various characteristics, and the functions it has, so that the provisions of agricultural zakat can be applied in issuing zakat on agricultural commodities. Then in terms of maslahah and maqasid shari'ah, the obligation of zakat on agricultural commodities can help fulfill the needs of the poor in particular, and mustahik zakat in general.Komoditas pertanian dewasa ini mengalami pertumbuhan dan perkembangan yang sangat pesat dengan inovasi pertanian yang baru seperti tanaman cangkok, tanaman hasil perkawinan silang hingga pertanian yang lebih modern yaitu hidroponik. Di mana hasil pertanian tersebut mampu meningkatkan penghasilan para petani secara signifikan. Hasil pertanian dalam hukum Islam adalah salah satu jenis harta yang wajib zakat. Tetapi, dali-dalil yang mengatur tentang zakat pertanian hanya menyebutkan beberapa hasil pertanian yang wajib zakat diantaranya, Jawawud, Gandum, Kusrma dan Kismis, maka secara tidak langsung hasil komoditas pertanian tidak tersentuh sama sekali di dalam dalil tersebut sehingga tidak ada ketetapan hukumnya. Tujuan dari penlitian ini adalah untuk melihat bagaimana penentuan ketentuan hukum dari zakat hasil komoditas pertanian atau perkebunan. Penelitian ini dilakukan dengan menggunakan studi literatur. Berdasarkan analisis yang dilakukan, hasil penelitian ini menunjukkan bahwa hasil komoditas pertanian yang memiliki nilai ekonomis tinggi di-qiyās-kan pada jenis buah-buahan dan biji-bijian wajib zakat yang disebutkan dalam dalil-dalil al-Qur’ān dan Sunnah dengan berbagai sifat dan fungsi yang dimilikinya, sehingga ketentuan-ketentuan zakat pertanian dapat diberlakukan dalam mengeluarkan zakat hasil komoditas pertanian. Kemudian dilihat dari segi maslahah dan maqāṣid syarī’ah, kewajiban zakat komoditas pertanian dapat membantu terpenuhinya kebutuhan fakir miskin khususnya, dan mustahik zakat pada umunya.